An Update in Adult Intraosseous Infusion - Sombatthavoankun, Wirot (Asian Medical Journal and Alternative Medicine, 2024)
The Intraosseous (IO) needle was developed in 1920s to access the vascular system via the bone marrow cavity. Around the 2010s, there was widespread interest in IO after the American Heart Association (AHA) recommended that intraosseous access is an optional route when intravenous (IV) access cannot be obtained quickly. IO had a higher success rate (99.6%), was faster to perform (15-24 seconds), had a nearly equal flow rate (1-5L/hr), and had almost equal drug bioavailability to IV. The complication of IO becoming dislodged was 10-16%, needle dislocation was 0.8%, needle bending was 0.4% and parafusion (defined as fluid leakage at the insertion site causing tissue edema surrounding the leakage point) was 0.4%. Most retrospective trials and meta-analysis studies found that hospital discharge, return of spontaneous circulation (ROSC), and favorable neurological outcome was higher with IV than with the IO group. In conclusion, IO is still beneficial for immediate vascular access and should be placed after and/or simultaneously to IV insertion. Objectives: to update content of adult intraosseous infusion in critical situations.